Estimation of Serum Iron in the Patients of Oral Submucous Fibrosis - Sasui Soonh Tahir, Muhammad Shahzad, Uzma Tariq, Shirjeel Husain, Bhavesh Maheshwari, Navid Rashid Qureshi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the serum levels of iron in Oral Submucous Fibrosis (OSMF) and normal healthy subjects. Subject and Methods: A total of 120 patients with symptoms and signs suggestive of OSMF equally divided into two groups named group A and B. Patients satisfying the insertion norms and those who has oral sub mucous fibrosis and the control group who are willing to get participate and getting done their blood tests for other purpose were asked for additional iron serum test for our research purpose. The demographic and medical factors like gender, pain, age, and medical record was known and logged in proforma. Diagnosis was done on clinical basis and was categorized according to progress then blood sample was obtained. The data was examined using SPSS version 20.0. Results: Control group's descriptive (standard/healthy) statistics indicate the mean iron levels of iron 94.13 ug/dl, while standard deviations are 17.57ug/dl. On the 1st day, 2nd day and 3rd day serum levels are examined, which reveal the mean values of 28.02, 22.81 and 24.0 ug/dl, respectively. The findings indicate a greater average of iron (17.57) in the healthy group (group B), while considerably less mean of iron level (6.47) in patients who have OSMF (group A). Conclusion: The study concluded that OSMF have lower levels of the iron in the serum while higher levels in the healthy group. Keywords: Serum Iron Level, Oral Submucous Fibrosis, Estimation